Enhancing Students’ Critical Thinking Skills through Problem-Based Learning in Science Education - Nabila, Chelsea Eka Putrista; Dea Santika Rahayu; Ahmad Muhlisin (Universitas Tidar, 2025)
Critical thinking skills are an essential aspect that students must possess in order to face the challenges of 21st century learning, especially in science learning, which is complex and requires in-depth analysis. Observations at SMP Negeri 1 Tempuran show that students' critical thinking skills are still relatively low. This condition is influenced by the implementation of a learning model that is not yet optimal and the dominance of the teacher's role in the learning process. An alternative solution that can be used is the Problem Based Learning (PBL) model, which places students at the center of learning by using contextual problems to trigger critical thinking. This study aims to determine the effectiveness of the PBL model in improving the critical thinking skills of junior high school students in science learning. The research method used a quantitative approach with a quasi-experimental design of the non-equivalent control group type. The sample consisted of class VII G as the experimental class and class VII F as the control class. The instrument was an essay test consisting of 10 questions that had been validated and tested for reliability. The data were tested for normality and homogeneity, then hypothesis testing was conducted using an independent sample t-test and N-Gain analysis. The results showed that the significance value was 0.011 < 0.05, and the N-Gain of the experimental class was 0.46 (moderate category), and that of the control class was 0.29 (low category). The conclusion of this study is that the PBL model is effective in improving students' critical thinking skills in science learning in junior high school.